CLASSROOM ACTIVITIES FOR TEACHING SPEAKING: VOICES OF INDONESIAN EFL LEARNERS - Nugroho, Arif; Nartiningrum, Novrika (Jurnal Pendidikan Bahasa, 2020)
Among the four English skills, oral communication becomes crucial for undergraduate students to be more competitive in the work-places. In a foreign language teaching, designing appropriate classroom activities is a prerequisite for the success of a language learning. Therefore, this study sheds some light on 92 EFL learnersâ€™ perceptions and insights of classroom activities for teaching speaking. Drawing on the data obtained from questionnaire and focus group discussion (FGD), the findings illustrated that the students held moderately positive perceptions toward the speaking activities in their classroom. In addition, the results of FGD revealed some insights from the students with regard to the ideal classroom activities for teaching speaking. The findings of this study provide insights for EFL teachers in designing appropriate classroom activities to achieve the success of teaching speaking.Â